2013
DOI: 10.1002/j.0022-0337.2013.77.3.tb05479.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Prototyping and 3D‐Virtual Models for Operative Dentistry Education in Brazil

Abstract: Many dental students struggle for visual recognition when irst exposed to the study of tooth cavity preparation in the operative dentistry laboratory. Rapid prototypes and virtual models of different cavity preparations were developed for the incoming irst-year class of 2010 at the Dental School of Federal University of Uberlândia, Brazil, to help them to visualize the subtle differences in cavity preparations and are described in this article. Rapid prototyping techniques have been used in dental therapy, mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 12 publications
0
48
0
6
Order By: Relevance
“…The external contour of the whole tooth was generated by scanning it with a contact profilometer (MDX‐40, Roland Co, Osaka, Japan). The root surface was then covered with utility wax, and the crown (enamel) was dipped in 10% hydrochloric acid solution for 10 minutes, before the remaining tooth structure (including the exposed dentino‐enamel junction and the intact root surface) was rescanned as described previously . Finally, the tooth was sectioned longitudinally using a precision saw and the contours of the pulp chamber on both sections were rescanned.…”
Section: Methodsmentioning
confidence: 99%
“…The external contour of the whole tooth was generated by scanning it with a contact profilometer (MDX‐40, Roland Co, Osaka, Japan). The root surface was then covered with utility wax, and the crown (enamel) was dipped in 10% hydrochloric acid solution for 10 minutes, before the remaining tooth structure (including the exposed dentino‐enamel junction and the intact root surface) was rescanned as described previously . Finally, the tooth was sectioned longitudinally using a precision saw and the contours of the pulp chamber on both sections were rescanned.…”
Section: Methodsmentioning
confidence: 99%
“…Hypothesis-driven studies using trainees as subjects have reported high satisfaction in operative dentistry, where 40 students used 3Dprinted models versus standard schematics and photographs for cavity preparation (44). Printed models have enhanced the learning performance of veterinary students (111).…”
Section: Educationmentioning
confidence: 99%
“…B. bei der Herstellung von OP-Splinten durch RP-Verfahren im Vergleich zur konventionellen Herstellung ist derzeit nicht zu erwarten [37]. Neben den Auswirkungen in der klinischen Tätigkeit werden die neuen technischen Grundlagen aber auch die Ausbildung der Studierenden verändern [38].…”
Section: Daten In Der Cloud?unclassified